Development and Evaluation of Antifungal Novel Polyherbal Cream using Eucalyptus globulus and Ocimum tenuiflorum - Suman, Shweta Shivshankar; Pingale, Rupesh; Hujare, Aditi Kishor; Darji, Fatima Samir; Bhor, Sakshi Dattatray (Journal of Neonatal Surgery, 2025)
This study evaluates the phytochemical properties, organoleptic features, and antimicrobial activity of Eucalyptus globulus and Ocimum tenuiflorum (Tulsi), along with a formulation cream containing both oils. Phytochemical tests revealed that Ocimum tenuiflorum contained alkaloids, flavonoids, and phenolic compounds, while Eucalyptus globulus lacked alkaloids and flavonoids but contained terpenoids and saponins in both species. The formulation cream exhibited desirable organoleptic features such as a smooth texture, easy application, and non-irritancy, with a pH of 5.83. Antimicrobial activity was assessed through zones of inhibition against Escherichia coli, Candida albicans, and Aspergillus niger. Eucalyptus globulus showed the highest activity against E. coli (22 mm), while the combination of both oils exhibited enhanced antifungal activity. The cream formulation displayed moderate antimicrobial activity, with zones of inhibition of 20 mm against E. coli and 18 mm against Candida albicans. These findings suggest that both oils have significant antimicrobial potential, with the cream formulation serving as a promising candidate for topical applications in skincare